Earth's future climate and its variability simulated at 9 km global resolution - J.-Y. Moon; J.-Y. Moon; J. Streffing; J. Streffing; J. Streffing; S.-S. Lee; S.-S. Lee; T. Semmler; T. Semmler; M. Andrés-Martínez; M. Andrés-Martínez; J. Chen; et al. (Earth System Dynamics)
Earth's climate response to increasing greenhouse gas emissions occurs on a variety of spatial scales. To assess climate risks on regional scales and implement adaptation measures, policymakers and stakeholders often require climate change information on scales that are considerably smaller than the typical resolution of global climate models (O(100 km)). To close this important knowledge gap and consider the impact of small-scale processes on the global scale, we adopted a novel iterative global earth system modeling protocol. This protocol provides key information on earth's future climate and its variability on storm-resolving scales (less than 10 km). To this end we used the coupled earth system model OpenIFS–FESOM2 (AWI-CM3; Open Integrated Forecasting System – Finite volumE Sea ice–Ocean Model) with a 9 km atmospheric resolution (TCo1279) and a 4–25 km ocean resolution. We conducted a 20-year 1950 control simulation and four 10-year-long coupled transient simulations for the 2000s, 2030s, 2060s, and 2090s. These simulations were initialized from the trajectory of a coarser 31 km (TCo319) SSP5-8.5 transient greenhouse warming simulation of the coupled model with the same high-resolution ocean. Similar to the coarser-resolution TCo319 transient simulation, the high-resolution TCo1279 simulation with the SSP5-8.5 scenario exhibits a strong warming response relative to present-day conditions, reaching up to 6.5 °C by the end of the century at CO2 levels of about 1100 ppm. The TCo1279 high-resolution simulations show a substantial increase in regional information and climate change granularity relative to the TCo319 experiment (or any other lower-resolution model), especially over topographically complex terrain. Examples of enhanced regional information include projected changes in temperature, rainfall, winds, extreme events, tropical cyclones, and the hydroclimate teleconnection patterns of the El Niño–Southern Oscillation and the North Atlantic Oscillation on scales of less than 1000 km. The novel iterative modeling protocol that facilitates coupled storm-resolving global climate simulations for future climate time slices offers major benefits over regional climate models. However, it also has some drawbacks, such as initialization shocks and resolution-dependent biases and climate sensitivities, which are further discussed.